2020
DOI: 10.1007/s00268-020-05555-6
|View full text |Cite
|
Sign up to set email alerts
|

Local Anaesthesia Alone Versus Regional or General Anaesthesia in Excisional Haemorrhoidectomy: A Systematic Review and Meta‐Analysis

Abstract: Background Excisional haemorrhoidectomy has been traditionally performed under general or regional anaesthesia. However, these modes are associated with complications such as nausea, urinary retention and motor blockade. Local anaesthesia (LA) alone has been proposed to reduce side effects as well as to expedite ambulatory surgery. This systematic review aims to assess LA versus regional or general anaesthesia for excisional haemorrhoidectomy. Methods A systematic review was conducted according to the Preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…Despite urinary retention complicates up to 50% of patients undergoing anorectal surgery under spinal anesthesia (27,28), particularly those undergoing hemorrhoidectomy (29), in our series no cases of urinary retention were recorded. The absence of episodes of urinary retention in this study may be related to the use of LA; in fact, Xia et al (13), in their meta-analysis, reported a significantly reduced risk of urinary retention after the procedure performed under LA compared to general or spinal anesthesia.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Despite urinary retention complicates up to 50% of patients undergoing anorectal surgery under spinal anesthesia (27,28), particularly those undergoing hemorrhoidectomy (29), in our series no cases of urinary retention were recorded. The absence of episodes of urinary retention in this study may be related to the use of LA; in fact, Xia et al (13), in their meta-analysis, reported a significantly reduced risk of urinary retention after the procedure performed under LA compared to general or spinal anesthesia.…”
Section: Discussionmentioning
confidence: 54%
“…Several meta-analyses demonstrated that MMH performed under LA is associated with significantly lower postoperative pain within 24 h after surgery and a lower need for painkiller drugs compared to general or spinal anesthesia (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preferred anesthetic techniques could vary among patients, surgeons, hospitals, and countries. Effects of anesthetic techniques on post-hemorrhoidectomy pain have been extensively examined in at least 18 RCTs with a total number of 1465 patients [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. A recent systematic review and meta-analysis of seven RCTs comprising 440 patients undergoing excisional hemorrhoidectomy (222 patients with local anesthesia plus intravenous sedation, and 218 patients with spinal anesthesia) has found that local anesthesia combined with intravenous sedation had a significantly lower pain score at 6 h and 24 h after an operation–with mean difference of numerical pain rating scale −2.25 (95% CI −3.26 to −1.24) and −0.87 (95% CI −1.33 to −0.40), respectively [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, PNB is a common efficient analgesic strategy used after hemorrhoidectomy. In comparison with other recent studies, our perspective focuses on the three main aspects of PNB anesthesia in analgesia, alleviation of complications and reduction of side effects after hemorrhoid surgery (29,30). PNB has its unique advantages due to the special anatomical structure.…”
Section: Discussionmentioning
confidence: 99%